MODEL KEWIRAUSAHAAN SOSIAL PADA LEMBAGA AMIL ZAKAT DI LIHAT DARI SUDUT PANDANG BISNIS - Waldelmi, Idel; Aquino, Afvan (Komunitas Manajemen Kompetitif, 2024)
An approach that combines entrepreneurial principles with a social mission to have a positive impact on society, especially through the management of zakat funds. In this context, amil zakat institutions not only act as collectors and distributors of zakat, but also as agents of change who initiate sustainable programs that can improve the welfare of the community at large. There is a uniqueness of social entrepreneurship practiced in amil zakat institutions. This study used a sample of 200 administrators of amil zakat institutions in Pekanbaru City and was collected using an online questionnaire. Data were analyzed using descriptive techniques. The results showed that the social entrepreneurship that has been carried out by managers in the Riau province Amil Zakat Institution can be said to be good although there must still be continuous evaluation to improve the ability of social entrepreneurship in the ranks of the administrators.